2019 Social Accounting Matrix for Egypt - Central Agency for Public Mobilization and Statistics; International Food Policy Research Institute (International Food Policy Research Institute, 2021)
The 2019 SAM for Egypt builds on the previous 2014/15 SAM that was built and published by Central Agency for Public Mobilization and Statistics (CAPMAS) with the support of the International Food Policy Research Institute (IFPRI). The updated SAM also relies on information from the Supply and Use Tables and the Economic Census for 2017/18 that were produced by CAPMAS. It includes 69 sectors and 73 products. The SAM also includes 13 factors of production in three broad categories: labor, land, and capital. Labor is disaggregated across rural and urban areas and into four education-based categories. Capital is disaggregated into four subcategories: crops, livestock, mining, and other. The SAM has ten household groups that are disaggregated by national per capita expenditure quintiles, then split into rural and urban households. Overall, the 2019 SAM is composed of 177 rows x 177 columns.